Chirality‐Assisted High‐Efficiency Metasurfaces with Independent Control of Phase, Amplitude, and Polarization. Issue 4 (9th December 2018) - Xu, He‐Xiu; Hu, Guangwei; Han, Lei; Jiang, Menghua; Huang, Yongjun; Li, Ying; Yang, Xinmi; Ling, Xiaohui; Chen, Liezun; Zhao, Jianlin; Qiu, Cheng‐Wei
Abstract: Simultaneously independent control of phase, amplitude, and polarization is pivotal yet challenging for manipulating electromagnetic waves by transmissive metasurfaces. Huygens' metasurface affords a high‐efficiency recipe primarily by engineering phase‐only meta‐atoms, restricting itself from realizing unprecedentedly complex functions of the transmission beam. Here, a 3D chirality‐assisted metasurface concept relying on integrated magnetoelectric meta‐atoms is proposed. It empowers the completely decoupled and arbitrary control of phase and amplitude at large incident angles and arbitrary polarizations. This strategy thus facilitates very sophisticated beam manipulations at close‐to‐unity cross‐polarized efficiency via trilayer integrated resonators with mutual twist. The prescribed phase coverage can be determined by geometrical footprints of the unit cell, while the global azimuthal twist unlocks the capability of tuning amplitudes without affecting the phase. The concept and significance of it are validated to implement several proof‐of‐prototype demanding functionalities by thin metasurfaces of λo /12, which generate self‐accelerating diffraction‐free Airy beams, lateral and axial dual focusing, and even specific multiplexed beam shaping, respectively. This finding opens up an alternative way in very fine control of light with minimalist complexity and advanced performance. It can stimulate novel and high‐performance versatile photonic metadevices, thanks to the fully independent control of phase, amplitude, and polarization. Abstract : The decoupling of amplitude, phase and polarization is analogous to the mechanical counterpart of three‐gear systems. The traditional dilemma is that tuning of either part will automatically affect the rest. This locks up metasurface functions and thereby limits its potentials. Now the authors' concept unlocks those "gears" such that each could be independently tuned, providing unprecedented access to the flatland of high‐efficiency metasurfaces.